Out-of-the-blue Names of Paint Colors - Jan Tent (Names, 2018)
Names of products play a significant role in their marketing, and are designed to express images with which buyers can identify. Manufacturers therefore pay close attention to their product names in order to maximize sales and to distinguish their products from those of competitors. The meaning of a product name would appear to be a crucial factor in its choice. A product designed for a specific consumer would benefit from a transparent or trendy name recognized and appreciated by the intended buyer. However, this tenet does not seem to apply to paint color names. Often these names tend to be enigmatic. This paper investigates the color names of 10 paint manufacturers in Australia and New Zealand. More than 10,700 color names were collected, classified, and quantitatively analyzed. The majority of names had enigmatic labels. The reasons for this are explored.